Analisis Pengaruh Opini Audit, Ukuran Perusahaan Klien, Kesulitan Keuangan Perusahaan, Ukuran KAP, DAN Pergantian Manajemen Terhadap Auditor Switching (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2010-2014) - Wicaksono, Bagus; , Drs. Wahyono.,MA,Ak (2017)
This research aims to analyze the effect of the audit opinion, the size of the client company, the company's financial difficulties, the size of the hood, and the turn against management auditor switching. This research is descriptive research quantitative research. The population in this research is the entire manufacturing company on the Indonesia stock exchange (BEI) in 2010-2014. Sample pengabilan method with the method of purposive sampling. The results showed the opinion of Audit (OA) does not affect the switching Auditors. The significance of value (1000) > 0.05. The size of the client company (UPK) has no effect against the auditor switching. the significance of value (0.903) > 0.05. The company's financial difficulties (CTF) have no effect against switching Auditors is indicated by the value of significance (0.220) > 0.05. The size of the HOOD (UKAP) has effect against the auditor switching. the significance of value (0.014) > 0.05. Changing of Management (PM) no effect on switching Auditors is indicated by the value of significance (0.510) > 0.05